Pengaruh Perbandingan Level Tepung Gamal (Gliricidia sepium) dan Tepung Lamtoro (Leucaena leucocephala) terhadap Kualitas Fisik Wafer sebagai Pakan Ternak Ruminansia Kecil - Adriana Soi (JAS, 2020)
The availability of animal feed in sufficient quantity and quality and sustainability is one of the factors that determines the success of the development of ruminants. One of the feed processing that can be made is making wafers. Wafers are one of the effective feed processing technologies and are expected to maintain the continuity of feed availability, especially in the dry season.The purpose of this study was to determine the physical quality of wafers made by comparing the levels of gamal flour and lamtoro flour as small ruminant feed. The variables measured in this study were density, water content, color and aroma. The materials used in this study were Gliricidia sepium, Leucaena leucocephala, fine bran, corn flour, mineral mix, starch flour, water. The method used is a Completely Randomized Design with variations of treatment as follows: R1 = 20% Gliricidia sepium + 60% Leucaena leucocephala + 8% Corn Fine Bran + Mineral Mix 2%, R2 = 40% Gliricidia sepium + 40% Leucaena leucocephala + Fine Bran 10% + Corn 8% + Mineral mix 2%, R3 = Gliricidia sepium 60% + Leucaena leucocephala 20% + Fine bran 10% + Corn 8% + % Mineral mix 2, R4 = Gliricidia sepium 80% + Leucaena leucocephala 0% + 10% fine bran + Corn 8% + Mineral mix 2%. It was concluded that making wafers for small ruminants with different levels of Gliricidia sepium and Leucaena leucocephala produced different density values with the highest density in the ratio of 40% Gliricidia sepium and 40% Leucaena leucocephala (R2) ie 0.41 g / cm³, while the water content values, the color and flavor are the same for all treatments.